Impact of Learner Support Services on Students’ Motivation to Learn in Ogun State Study Centres of the National Open University of Nigeria - ADEKUNLE, Akeem Ayotunde; ADEYANJU, Jacob Alabi (Ilorin Journal of Education, 2023)
This study investigated the effectiveness of the learner support services in promoting students’ motivation to learn in the Ogun State study centres of the National Open University of Nigeria (NOUN). Two research hypotheses were tested in the study. A descriptive survey research design of ex-post-facto was used for the study. The population comprised all the 5893 active students at the Abeokuta and Awa Ijebu Community NOUN Study Centre of Ogun State. The sample size comprised 848 students selected through simple random sampling technique. A 32-item research instrument with reliability coefficient of .93 titled “Effectiveness of Learner Support Services and Students’ Motivation to Learn Questionnaire” (ELSSSMTLQ) was designed by the researchers and validated by lecturers in Educational Management and Measurement and Evaluation to collect data for the study. Data collected were analysed using One Way Analysis of Variance to test the two hypotheses at 0.05 level of significance. The result showed that the provision of Learner Support Services had significant impact on students’ motivation to learn, with the highest effect manifesting between high and moderate extent. There was also a significant impact of students’ attitudes towards the utilization of learners’ support services and their motivation to learn with the highest effect manifesting between negative and neutral attitudes. It was recommended that management of NOUN should provide adequate learner support services in the study centres, in addition to provision of adequate orientation to students on the effective utilization of their support services.